Clinicopathological and Immunological Changes in Indian Post Kala-Azar Dermal Leishmaniasis (PKDL) Cases in relation to Treatment: A Retrospective Study. (18th May 2015) - Verma, Neena; Bimal, Sanjiv; Das, Vidya Nand Rabi; Pandey, Krishna; Singh, Dharmendra; Lal, Chandra Shekhar; Singh, Ashish Kumar; Sinha, Prabhat Kumar; Das, Pradeep
Abstract : Post-kala-azar dermal leishmaniasis (PKDL) is an important factor in kala-azar transmission; hence its early detection and assessment of effective treatment is very important for disease control. In present study on 60 PKDL cases presented with macular, mixed papulonodular, or erythematous lesions, Leishmania parasites were demonstrated microscopically in 91% of papulonodular and 40% of macular lesions. Cellular infiltrates in skin biopsy imprint smears from lesions were mononuclear cells, 25–300/OIF (oil immersion field), predominantly histiocytes with vacuolation, many lymphocytes, some plasma cells, and Leishmania amastigotes 0–20/OIF. Cases with no demonstrable parasites were diagnosed on the basis of past history of VL, lesion's distribution, cytopathological changes, and positive DAT (86.83%). Following antileishmanial treatment with SAG, papulonodular forms of PKDL lesions disappeared clinically but microscopically the mononuclear cells (20–200/OIF) persisted in the dermal lesions. Response observed in macular PKDL lesions was poor which persisted both clinically and cytopathologically. Follow-up of PKDL will assess the effectivity of treatment as either disappearance of lesions or any relapse. Studies on involvement of immunological factors, that is, certain cytokines (IL-10, TGF- β, etc.) and chemokines (macrophage inflammatory protein, MIP 1-α, etc.) in PKDL, may provide insight for any role in the treatment response.